Pelatihan dan Pendampingan Penulisan Karya Ilmiah Bagi Guru dan Staff di SMK Nahdlatul Wathan Diniyah Islamiah Korleko - Yahya, Yahya; Bahtiar, Hariman; Nur, Amri Muliawan; Sadali, Muhamad; Putra, Yupi Kuspandi; Fathurrahman, Fathurrahman; Sutriandi, Aswian Editri; Nurhidayati, Nurhidayati; Samsu, L. Muh.; Saiful, Muhammad (Jurnal Teknologi Informasi untuk Masyarakat, 2023)
Nahdlatul Wathan Diniyah Islamiah Korleko Vocational High School is one of the Vocational High Schools under the Hamzanwadi Education Foundation Darunnahdlatain Nahdlatul Wathan Diniyah Islamiah Pancor Islamic Boarding School. This school was founded to meet the demands and needs of the community, especially in the Labuhan Haji District area. NWDI Korleko Vocational School has 2 departments, namely the Department of Computer and Network Engineering (TKJ) and the Department of Multimedia. NWDI Korleko Vocational School is guided by many teaching staff who have various scientific disciplines. Even productive teachers are taught by teachers who have scientific disciplines that are very different from the competencies that must be taught. Starting from the diversity of scientific disciplines of teachers which greatly influences the competence of their students. The diversity of scientific disciplines is what creates non-uniformity in information technology knowledge, especially in the field of writing scientific papers. There are those who understand and there are those who don't understand at all. That is what causes the desire to help understand techniques and how to apply information technology in writing scientific papers. From the initial test analysis in information technology knowledge, the average teaching staff at NWDI Korleko Vocational School understands around 40% to 50% of scientific writing. After training and mentoring, there was a significant increase in the writing and application of information technology in writing scientific papers, reaching 80% to 90%, 10% of whom did not understand, which was because during the training and mentoring, the teaching staff had a high level of attendance. less than 70%. Thus, there needs to be ongoing training and mentoring so that teaching staff can understand everything